2018
DOI: 10.1051/epjconf/201818301008
|View full text |Cite
|
Sign up to set email alerts
|

Strain-rate effects associated with the HJC concrete model

Abstract: The Holmquist-Johnson-Cook (HJC) model for concrete was presented in 1993 and has been used extensively since that time. Since then a third invariant effect has been added and the shear modulus has been revised to vary such that Poisson's ratio is held constant. It has always been diffcult, however, to determine the appropriate constant for the strain-rate effect as most of the published data are for the net stress as a function of the strain rate. Because concrete is both pressure dependent and strain-rate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Johnson’s method for penetration and perforation problems. 16 According to, 17 the numerical method contains a new way to isolate discontinuity surfaces of materials that does not impose serious restrictions on the solution of the problems. For example, the crater depth obtained from the numerical study differs by less than 10% from experimentally obtained values, 18 a good agreement.…”
Section: A Mathematical Model and A Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson’s method for penetration and perforation problems. 16 According to, 17 the numerical method contains a new way to isolate discontinuity surfaces of materials that does not impose serious restrictions on the solution of the problems. For example, the crater depth obtained from the numerical study differs by less than 10% from experimentally obtained values, 18 a good agreement.…”
Section: A Mathematical Model and A Numerical Methodsmentioning
confidence: 99%
“…Several quantitative tests have been performed in. 3,12,16 In addition, several experiments 12,13 were repeated. The subject of comparison was the residual displacement of metal plate subjected impact of an ice cylinder.…”
Section: Test Calculationsmentioning
confidence: 99%
“…Regarding the strain-rate formulation in MHJC material model, Polanco-Loria et al [32] modified the original strainrate function to avoid negative rate enhancement predicted by the HJC model for low strain rates. In 2018, Johnson et al [60] argued that new experimental data showed that the strain-rate enhancement effects in concrete were greater than previously determined for the HJC model. When compared to material data available in the literature [61] for different concrete types, we see that the non-linear formulation with C = 0.04 as used by Polanco-Loria et al [32] provides reasonable results.…”
Section: Discussionmentioning
confidence: 97%
“…All three models are readily available as standard models in the explicit finite element (FE) code LS-DYNA (LST, 2020). The Holmquist–Johnson–Cook (HJC) model (Holmquist et al, 1993; Johnson et al, 2018; Rajput et al, 2018) is another widely used model, and a modified version has been included due to its relative ease of calibration (Polanco-Loria et al, 2008). Numerous constitutive concrete models may be employed to simulate the ballistic impact resistance of concrete, for example, the Winfrith Concrete (WC) model (Broadhouse and Neilson, 1987), Concrete-Damage-Plasticity (CDP) (Lubliner et al, 1989) and a damage model based on effective rate-dependency proposed by Pereira et al (2018).…”
Section: Introductionmentioning
confidence: 99%